Kontribusi Produksi Padi Sawah Daerah Sentra Bosowa Terhadap Produksi Padi Sawah di Sulawesi Selatan - Rikayanti Rikayanti; Arifin Arifin; Abd. Asis Pata (Universitas Muslim Maros, 2021)
This research was conducted in Bone District, Soppeng, Wajo in South Sulawesi. This location was chosen with the consideration that it has been managing the Rice Field for a long time. The data used are: secondary data, namely data obtained from agencies / institutions related to or related to this research. The objectives of this study were: The purpose of this study was to determine the contribution of lowland rice production in the center of Bosowa (Bone, Soppeng, Wajo) to lowland rice production in South Sulawesi. The collected data is then tabulated to obtain real data which is used for analysis purposes. This study used a quantitative descriptive analysis method to determine the amount of income obtained by farmers from the contribution of lowland rice production in the Bosowa area to lowland rice production in South Sulawesi. The results showed that the amount of income obtained by farmers from the contribution of lowland rice production in the center of Bosowa area was 1,792,509,419 to lowland rice production in South Sulawesi as much as 55,045,131.00. The results of the calculation have been able to produce lowland rice production in the Bosowa center area in South Sulawesi.